Have the changes in product claims due to the global pandemic been effective in the consumer minds in the Portuguese fast moving consumer goods market? - Tavares, Bárbara Cloé Carvalho (2022)
With the rise of a global pandemic, consumers are more concerned about their health, therefore seeking products which can suffice those needs. Product claims can help companies respond to the current demand. This study analyzed a survey(n=65) in which consumers were given three choices (a no claim product, afreecovid-19 claim product and akills99.9%of virus and bacteria claim product) with variances in pricing. There is evident preference for the 99.9% claim product, additionally consumers are also willing to pay up to at least 50% more than the original product for an additional benefit.